Effectiveness of Electronic Partograph Compared to Manual Partograph in Improving Labor Documentation in Independent Midwife Practice - Larasati, Timmy; Dioso, Regidor III; Dewi, Ratna; Dielsa, Maya Fernanda; Azhari, Armita Sri (PT. Riset Press International, 2025)
Partograph is an important tool in labor management that aims to monitor the progress of the labor process and identify potential complications. In today's digital era, the use of electronic partographs has begun to be introduced as an alternative to manual partographs. This study aims to explore the effectiveness of electronic partographs compared to manual partographs in improving labor documentation in independent midwife practices. This study used a qualitative approach with in-depth interviews with 30 independent midwives who used both types of partographs in their practice. Data were collected from direct observation and document analysis to assess the quality of labor documentation produced. Analysis was carried out using thematic analysis methods to identify key themes that emerged from the data. The findings showed that 90% of electronic partographs improved the accuracy and consistency of documentation compared to manual partographs. Most midwives reported ease in accessing and storing data, as well as the ability to reduce human error. However, several obstacles related to technology accessibility and training needs were also identified. The use of electronic partographs in independent midwife practices shows significant potential in improving labor documentation. Despite challenges in implementation, the benefits gained in terms of accuracy and efficiency support further adoption of this technology in maternal health practice.